Peran Dinas Tenaga Kerja dan Transmigrasi Provinsi Jawa Timur dalam Perlindungan Hukum Atas Upah Pekerja - Aprilia Verlianti; Arimurti Kriswibowo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The government as an institution is responsible for providing the right to workers' wages and ensuring that the application of applicable regulations can be implemented properly. In this regard, Disnakertrans through the supervision sector, conducts monitoring related to the application of labor regulations. The East Java Provincial Manpower and Transmigration Office, through the field of supervision, aims to provide protection and fulfillment of workers' wages in accordance with the City / Regency Minimum Wage (UMK). The legal basis is Law No.13 of 2003 on Manpower, as a guideline for the Manpower Office to carry out its duties optimally. The purpose of this research is to find out how the role of the East Java Provincial Manpower and Transmigration Office in the legal protection of workers' wages as well as efforts that must be made in fulfilling legal protection of workers' wages, in labor protection in the East Java Province area. The type of research used is normative juridical with a qualitative approach method. This research uses primary and secondary data sources, where primary data is obtained from source information, namely labor inspector employees of the East Java Provincial Manpower and Transmigration Office. Data collection techniques were obtained through interviews, observations, and document studies to obtain research results. The results showed that the East Java Provincial Manpower and Transmigration Office has carried out its role optimally in providing legal protection for workers' wages